Fracture mechanics for membranes : The 15th European Conference of Fracture (ECF15) - Li, Chong; Espinosa, Rogelio; Ståhle, Per (ECF15-the 15th European Conference of Fracture - Advanced Fracture Mechanics for Life and safety Assessments, Stockholm, August 11-13, Stockholm, Sweden, 2004-08-11 - 2004-08-13, 2005)
During fracture of membranes loading often produces buckles above and below the crack surface. This changes the stress state surrounding the crack-tip and stresses in the neighbourhood of the crack-tip posses a weaker singularity than r -1/2. As a result, fracture occurs when the crack-tip stress distribution is different as compared with that when buckling is artificially prevented. Therefore the conditions for transfer of lab results to real structures are changed. The weaker singularity is here utilised to formulate an adopted fracture mechanical theory. An approximate application is made based on an assumption that the buckled area of the paper is incapable of carrying load. This region is approximated with the region that is under compressive load at plane stress conditions. The result is compared with experiments performed on paper. The importance of the linear extent of the process region has on the energy available for fracture is discussed.
Keywords: fracture; membranes; Stress intensity factors; buckling